PREVALENCE AND CLINICAL PHENOTYPES OF POLYCYSTIC OVARY SYNDROME IN ADOLESCENT GIRLS LIVING IN IODINE-DEFICIENT REGIONS (Multidisciplinary Journal of Science and Technology, 2026)
Polycystic ovary syndrome (PCOS) is one of the most common endocrine conditions affecting females of reproductive age, yet its recognition during adolescence remains methodologically challenging. Pubertal maturation is characterized by transient menstrual irregularity, acne, and multifollicular ovarian morphology—features that can overlap with PCOS and inflate prevalence estimates when adult criteria are applied without age-specific safeguards. Contemporary evidence demonstrates that adolescent PCOS prevalence varies substantially by diagnostic framework: meta-analytic data indicate higher estimates under the original Rotterdam criteria than under the stricter adolescent-oriented recommendations embedded within the 2023 International Evidence-Based Guideline.